HN125: A Novel Immunoadhesin Targeting MUC16 with Potential for Cancer Therapy - Xiang, Xinran (Ivyspring International Publisher, 2011)
Background: The mucin MUC16 expresses the repeating peptide epitope CA125 that has been known for decades to be a well-validated cancer marker that is overexpressed on the cell surface of ovarian cancers and other malignant tumors. In spite of recent efforts to make mouse monoclonal antibodies to MUC16 to treat ovarian cancer, a human monoclonal antibody against this mucin has not been described. MUC16 interacts with mesothelin, a protein that mediates heterotypic cancer cell adhesion, indicating that MUC16 and mesothelin play an important role in the peritoneal implantation and metastasis of ovarian tumors. Therefore, a suitable candidate for therapeutic targeting of MUC16 would functionally block the interaction of MUC16 and mesothelin. Methodology/Principal Findings: Here we report the generation of a novel immunoadhesin, HN125, against MUC16 that consists of a functional MUC16 binding domain of mesothelin (IAB) and the Fc portion of a human antibody IgG1. The yield for purified HN125 proteins is over 100 µg/mL of HEK-293 culture supernatant. We show that HN125 has high and specific affinity for MUC16-expressing cancer cells by flow cytometry and immunohistochemistry. HN125 has the ability to disrupt the heterotypic cancer cell adhesion mediated by the MUC16-mesothelin interaction. Moreover, it elicits strong antibody-dependent cell mediated cytotoxicity against MUC16-positive cancer cells in vitro. Conclusion/Significance: This report describes a novel human immunotherapeutic agent highly specific for MUC16 with potential for treating ovarian cancer and other MUC16-expressing tumors. Because of its lower immunogenicity in patients, a fully human protein is the most desirable format for clinical applications. We believe that the methods developed here may apply to the generation of other tumor-targeting immunoadhesins when it is difficult to obtain a human monoclonal antibody to a given antigen for clinical applications. The resultant immunoadhesins can have advantages usually found in monoclonal antibodies such as ease of purification, high binding affinity and effector functions.